Water Resource Software : Application Overview and Review - Borden, Carter (World Bank, Washington, DC, 2016)
This document provides an overview of how water resource software’s (WRS) are used to manage water resources issues, criteria for WRS selection, and a high level review of WRS currently available that central and state governments of India can use for water management. The water resource issues covered include water allocation and planning, flood management, groundwater management, conjunctive use, water quality, and sediment transport.